Religia jako ideologia. Status religioznawstwa i problem transcendencji - Paradowski, Ryszard (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2012)
The paper attempts to expand and transform the religious notion of transcendence, as well as the way in which religion is defined, which in Polish religious studies is dominated by a denominational approach, where the social functions of religion in particular (which according to academic religious studies determine the essential character of a religion) are considered ‘non-specific,’ while the ‘specific’ functions are those that the religion itself assumes to be such. The paper states that the essential character of religion goes beyond its social functions to encompass broadly understood ideological functions. This claim is illustrated by an analysis of the biblical story of the creation of the world and man, as this story demonstrates that religion is a product of the biblical axiological dilemma interpreted from an authoritarian viewpoint.
Religion as an ideology. The status of religious studies and the issue of transcendence